Microfiltration Membranes for Separating Oil / Water Emulsion - Faiq Al-Alawy, Ahmed; Mohsin Al – Musawi, Samah (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
This research was aimed to study the efficiency of microfiltration membranes for the treatment of oily wastewater and the factors affecting the performance of the microfiltration membranes experimental work were includes operating the microfiltration process using polypropylene membrane (1 micron) and ceramic membrane (0.5 micron) constructed as candle; two methods of operation were examined: dead end and cross flow. The oil emulsion was prepared using two types of oils: vegetable oil and motor oil (classic oil 20W-50). The operating parameters studied are: feed oil concentration 50 – 800 mg/l, feed flow rate 10 – 40 l/h, and temperature 30 – 50 oC, for dead end and cross flow microfiltration. It was found that water flux decreases with increasing operating time and feed oil concentration and increases with increasing operating temperature, feed flow rate and pore size of membrane. Also, it was found that rejection percentage of oil increases with increasing flow rate and rejection percentage decreases with increasing time, feed oil concentration, feed temperature and pore size of membrane for dead end and cross flow microfiltration. In cross flow microfiltration, reject concentration (concentrate) increases with increasing flow rate, feed concentration, time and feed temperature. The dead end filter has more flux compared to cross flow filter, while, in cross flow the oil rejection percentage is best than dead end. Flux for vegetable oil is more than motor oil but rejection percentage for vegetable oil is less than that for motor oil. The highest recovery ratio was found is 44.8% for cross flow process with recirculation of concentrating stream to feed vessel. The highest rejection percentage of oil was found is 98 % and 97.8 % for cross flow and dead ends respectively.